1989
DOI: 10.1680/geot.1989.39.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and centrifuge modelling of coupled heat flow and consolidation around hot cylinders buried in clay

Abstract: Britto (1984) presented a finite element formulation to analyse the coupled heat transfer–consolidation problem for a saturated fine-grained elastic soil. The formulation was validated by comparing it with analytical solutions for a soil layer heated on one side and a cylindrical heat source in an infinite medium. This Paper presents the results of the comparison of centrifuge test data and finite element analyses where the soil is treated as either purely elastic or elasto-plastic. In the centrifuge test, mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…This is possible owing to scaling laws derived by Savvidou (1988), who determined the time scaling factor of N 2 (N being the applied enhanced gravity in the centrifuge) for heat flow in accelerated gravity experiments, which enables multi thermal cycles to be simulated in a shorter duration (hours) that would normally take years at full field scale. Notable centrifuge investigations benefiting from this scaling relationship include Stewart and McCartney (2014), Ng et al (2014), Britto et al (1989), Goode et al (2014), and Stewart and McCartney (2012). These studies considered a range of various soil types with reported observations of increased pile settlements and ratcheting over several thermal cycles.…”
Section: Energy Geotechnicsmentioning
confidence: 99%
“…This is possible owing to scaling laws derived by Savvidou (1988), who determined the time scaling factor of N 2 (N being the applied enhanced gravity in the centrifuge) for heat flow in accelerated gravity experiments, which enables multi thermal cycles to be simulated in a shorter duration (hours) that would normally take years at full field scale. Notable centrifuge investigations benefiting from this scaling relationship include Stewart and McCartney (2014), Ng et al (2014), Britto et al (1989), Goode et al (2014), and Stewart and McCartney (2012). These studies considered a range of various soil types with reported observations of increased pile settlements and ratcheting over several thermal cycles.…”
Section: Energy Geotechnicsmentioning
confidence: 99%
“…(MODIFIED CAM CLAY : k = 2.5E-lOm/s) 8 times, at the end of heating and consolidation. This is to be expected for a linear elastic soil.…”
Section: Analysis B2mentioning
confidence: 99%
“…Smith and Booker, 1989;Britto et al, 1989). However, only the reversible volume change of the soil due to a change in temperature was considered in their models.…”
Section: Introductionmentioning
confidence: 99%